LINGUISTIC GENDER DYNAMICS: TRANSLATING GENDER IN WORLD LITERATURE (Academicia Globe: Inderscience Research, 2024)
This article delves into the intricate dynamics of linguistic gender in the realm of translation, focusing specifically on its portrayal in world literature. Gender, as a linguistic construct, extends beyond mere biological distinctions, encompassing a spectrum of identities and expressions that vary across cultures. Translating gender presents formidable challenges due to differences in linguistic structures and cultural contexts. This article explores these challenges, strategies, and implications involved in conveying gender identities across languages. It discusses the impact of grammatical gender, the lack of equivalent terms for non-binary identities, and the influence of cultural norms on translation decisions. Strategies such as footnotes, creative adaptation, and collaborative translation efforts are examined as means to navigate these complexities. The article emphasizes the importance of promoting gender diversity and inclusivity in literature through translations that respect the integrity of the source text while acknowledging the nuances of gender across languages and cultures. Ultimately, it argues that translators play a pivotal role in challenging stereotypes, amplifying diverse voices, and fostering a more inclusive understanding of gender in literature.